Implementation of SEO on Dusun Nusantara Web-based Application as Tourism Promotion Media - Ahmad Akbar; Indri Sulistianingsih; Fariz Harindra Syam; Bagus Kurniawan (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
This study explores the implementation of SEO on the Dusun Nusantara web-based application as a tourism promotion media. This implementation aims to increase the number of tourist visits to Desa Kota Pari by improving the website's ranking in search engines like Google. The study analyzes the Google Analytics data for the last 90 days to evaluate the effectiveness of SEO implementation. The results show that the implementation of SEO has successfully increased the number of users and sessions on the application, indicating an increase in user interest in visiting the application. However, the high bounce rate of 76.76% needs improvement. Despite this, the average session duration of 1 minute 29 seconds indicates that users are interested in exploring pages in the application. The study concludes that implementing SEO in the DusunNusantara.com application is an effective strategy for promoting tourism in the area. By utilizing a web-based application, managers can provide complete and accurate information about existing tourism in Desa Kota Pari and Pantai Cermin, which can expand the reach of tourism promotion and increase the number of tourists visiting Desa Kota Pari. However, it is essential to improve the application's content to make it more exciting and relevant and to provide a more engaging and interactive experience to the app to increase visitor session duration. Thus, implementing SEO in the Dusun Nusantara application can be an effective strategy for promoting tourism and increasing tourist visits to the area.